Promoting social transformation through basic social work training for the Nagari apparatus: a case study in West Sumatra - Siswati, Hermaini; Afrizal; Djafri, Defriman; Symon, Denas (BKM Public Health and Community Medicine, 2025)
Purpose: This study aims to analyze why social support has not yet successfully transformed parenting behavior among caregivers of stunted toddlers in Nagari Tanjung, West Sumatra, and to identify internal and external barriers that prevent caregivers from accessing and utilizing the available support. Methods: We used an exploratory qualitative approach with a case study design, involving 47 caregivers of stunted toddlers. The findings highlight parenting barriers and provide a compelling argument for promoting Basic Social Work Training (PDPS) among nagari officials, thereby enabling them to integrate various social components within their communities effectively. We collected data through in-depth interviews, participatory observation, and documentation, then thematically analyzed it based on internal and external factor categories. Data collection was conducted in Nagari Tanjung, West Sumatra, in 2024. Results: The main barriers include low nutritional literacy, stigma, shame, minimal father involvement, and beliefs in myths such as palasik. Social support from family, community, health workers, and the government has not been effective due to a lack of integration, inadequate cultural contextualization, and insufficient attention to psychosocial aspects. Moreover, the role of community social workers (PSM) at the village level has not been fully optimized, further exacerbating the situation. Conclusion: Community- and culture-based interventions are necessary, along with capacity-building for Nagari government officials through PDPS, to enable them to function similarly to social workers. The Ministry of Social Affairs should extend this training to the village or nagari level, not just at the provincial or district level. Strengthening the roles of nagari officials, village midwives, and community cadres (PKK, Posyandu, Family Planning, PPKBD, Human Development Cadres, PSM, and PKH facilitators) can help coordinate a sustainable and culturally contextual parenting support system.